Argentina facing the palestinian-israeli question : a study on the positions adopted by the Alfonsín administration (1983-1989) - Fabani, Ornela (2014)
Fil: Fil: Fabani, Ornela. Universidad Nacional de Rosario. Facultad de Ciencia Política y Relaciones Internacionales; Argentina.